AEGOPOGON (GRAMINEAE) IN MALESIA - J. F. Veldkamp (Research Center for Biology, 1984)
AeyopoyoiL ceucliroides Willd. var. cenchroides is recorded for the first time from Malesian area based on a collection from Mt. Michael (Papuu New Guinea). A description is provided.